Integrasi GIS pada Modul Alokasi Supir untuk Peningkatkan Efisiensi Layanan Rudi Rental Mobil Medan - Sabila Al Rizka (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The manual driver scheduling system in the “Mobil keluarga”Rudi car rental Medan business often faces conflicts and inefficiencies. Problems such as driver double-booking, where Driver A is scheduled to accompany Guest B while still serving Guest C, lead to service delays and customer dissatisfaction. This research aims to design and implement a driver allocation module integrated with a Geographic Information System (GIS) to optimize the scheduling process. The method used is Research and Development (R&D) with data collection through interviews and system design using UML and prototyping in Figma. The proposed system utilizes GIS to map driver locations in real-time and identify the nearest available driver to a customer, thereby reducing allocation decision time. It is hoped that this research can produce a system design that serves as a solution to improve service efficiency and operational productivity in Rudi car rental Medan businesses. The integration of GIS in driver allocation is the novelty of this study in the context of small and medium-sized rental businesses.